Children of the Affluent: Challenges to Well-Being - Luthar, Suniya S. (2005)
Growing up in the culture of affluence can connote various psychosocial risks. Studies have shown that upper-class children can manifest elevated disturbance in several areas—such as substance use, anxiety, and depression—and that two sets of factors seem to be implicated, that is, excessive pressures to achieve and isolation from parents (both literal and emotional). Whereas stereotypically, affluent youth and poor youth are respectively thought of as being at “low risk” and “high risk,” comparative studies have revealed more similarities than differences in their adjustment patterns and socialization processes. In the years ahead, psychologists must correct the long-standing neglect of a group of youngsters treated, thus far, as not needing their attention. Family wealth does not automatically confer either wisdom in parenting or equanimity of spirit; whereas children rendered atypical by virtue of their parents' wealth are undoubtedly privileged in many respects, there is also, clearly, the potential for some nontrivial threats to their psychological well-being.